Alterações no frênulo lingual e seus impactos no aleitamento materno - Campos, Sandra Mara Teixeira de Souza (2023)
Breastfeeding is the best way to feed the baby and should be exclusive for the first 6 months of life. The tongue plays a key role in sucking, swallowing and transporting food. Adequate sucking is an important factor that influences the practice of breastfeeding. For the extraction of milk, the sucking function of the newborn depends on an adequate functioning of the tongue, including the lingual frenulum. Ankyloglossia is a congenital anomaly that occurs when the remaining embryological tissues, which should have undergone apoptosis during embryonic development, remain on the underside of the tongue, restricting its movements. Thus, studies are needed to investigate and discuss the relationships or even interference of the lingual frenulum and difficulties in breastfeeding. The present study aimed to analyze changes in the lingual frenulum of babies and their repercussions on breastfeeding. Longitudinal study with a quantitative approach carried out with 13 (thirteen) mother-infant binomials selected in rooming-in with a score equal to or greater than 7 (seven) considered altered lingual frenulum according to the score of the Neonatal Screening Test recommended by the Frenulum Assessment Protocol Lingual. Data were collected in the first 30 days of life (time 01) and between 310 and 1800 (time 02). Obstetric data from the mother and variables related to breastfeeding were collected, in addition to the indication and performance of frenotomy. Data were analyzed using descriptive and analytical statistics using Fisher's Exact Test and Student's T Test. Of the 466 children born at term during the study period, 13 had ankyloglossia, with an incidence of 27 babies with alterations per 1000 born at term. In the present study, it was shown that whether or not to perform frenotomy was not statistically significant for the act of breastfeeding exclusively in relation to the variables in question. Thus, through this study, observing the results, we can conclude that there was no impact of the lingual frenulum in the practice of breastfeeding. It is important to point out that further studies are needed on the impact of ankyloglossia on breastfeeding, differentiating it from initial management difficulties, as well as standardization of evaluation and treatment. Also, greater training of professionals on the subject, so that they can help with difficulties that may occur and greater standardization of guidelines for family members. The findings of this study demonstrate that the topic related to oral frenulum has aroused a growing interest in the scientific community and highlight the concern to unveil the real impact of ankyloglossia on breastfeeding the baby, as well as the need to seek a consensus on the diagnosis regarding the indication surgical.